Time series assessment on landslide occurrences in an area undergoing development - Norbert Simon, Michael Crozier, Mairead Roiste, Abdul Ghani Rafe, . (2015)
his study assesses the influence of development on landslide occurrences in a rapidly developing area, Kota Kinabalu in Sabah Malaysia, across three assessment years (1978, 1994 and 2010). Two development indicators, land use and road density, were used to measure the influence of development on landslide occurrence.